A new proof of semicontinuity by Young measures and an approximation theorem in Orlicz-Sobolev spaces. (17th August 2003) - Bianconi, Barbara
Abstract : We give a new approach to study the lower semicontinuity properties of nonautonomous variational integrals whose energy densities satisfy general growth conditions. We apply the theory of Young measures and properties of Orlicz-Sobolev spaces to prove semicontinuity result.